On solving classes of differential equations with applications - Ibrahim Sulaiman, Mohammed; Mustafa, Mamat; Shadi, Al-Ahmad (2019)
Given the difficultly of applying the methods of variation of parameters and undetermined coefficients for many classes of differential equations and inspiration of the role of the Linear Differential Operators to solve classes of Differential equations. In this paper, we introduce the nested factorization technique for solving classes of Differential equations using the basic differentiation and integration approach. Numerical examples with encouraging results have been presented to illustrate the efficiency of the method.